Hormone replacement therapy and mid-term implant survival following knee or hip arthroplasty for osteoarthritis: a population-based cohort study. Issue 3 (22nd January 2014) - Prieto-Alhambra, D; Javaid, M K; Judge, A; Maskell, J; Cooper, C; Arden, N K
Abstract : Objectives: Osteolysis and subsequent prosthesis loosening is the most common cause for revision following total knee arthroplasty (TKA) or total hip arthroplasty (THA). Hormone replacement therapy (HRT) could reduce osteolysis through its antiresorptive effects. We studied whether HRT use is associated with reduced revision rates in a community-based cohort of women undergoing TKA or THA for osteoarthritis. Methods: Female participants in the General Practice Research Database undergoing a primary TKA or THA from 1986 to 2006 were included. We excluded patients aged <40 years at the date of primary, and those with a history of previous hip fracture or rheumatoid arthritis. Women with at least 6 months of HRT were identified as HRT users. We further explored the associations among HRT use of ≥12 months, adherence (medication possession ratio) and cumulative use and revision risk. Cox models were fitted to model implant survival in years. Propensity score matching was used to control for confounding. Results: We matched 2700 HRT users to 8100 non-users, observed for a median (IQR) of 3.3 (1.5–6.1) years after TKA/THA. HR for HRT ≥6 months was 0.62 (95% CI 0.41 to 0.94), whereas HR for ≥12 months was 0.48 (0.29 to 0.78). Higher adherence and therapy duration were associated with further reductions in revision rates. Preoperative HRT appeared unrelated to implant survival. Conclusions: HRT use is associated with an almost 40% reduction in revision rates after a TKA/THA. These findings require replication in external cohorts and experimental studies.